EXPLORING CONSUMER INSIGHTS THROUGH MULTIMEDIA IMAGE DATA FUSION IN E-COMMERCE - Anderson , Thomas (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
In the era of rapid e-commerce expansion, an increasing number of consumers are opting for online purchases to fulfill their daily needs. Nevertheless, the dynamics of online product marketing have gained recognition among scholars and ecommerce professionals. The study of consumer impulse shopping behavior is currently limited, both in terms of depth and breadth, with scattered research in various countries. In the context of China, there exists room for more comprehensive theoretical exploration. The escalating competition within the realm of online e-commerce intensifies the challenge of enterprises accurately comprehending consumer motivation and behavior. Consequently, this paper delves into the theoretical underpinnings of the influence mechanism on online e-commerce product purchase behavior. The proposed model provides a thorough understanding of the formation of online shopping impulse behavior, serving as a valuable resource for e-commerce practitioners in navigating this highly competitive landscape